2020
DOI: 10.1017/ice.2020.1273
|View full text |Cite
|
Sign up to set email alerts
|

Understanding viral shedding of severe acute respiratory coronavirus virus 2 (SARS-CoV-2): Review of current literature

Abstract: Objective: Transmission of SARS-CoV-2 has significant implications for hospital infection prevention and control, discharge management, and public health. We reviewed available literature to reach an evidenced-based consensus on the expected duration of viral shedding. Design: We queried four scholarly repositories/search engines for studies reporting SARS-CoV-2 viral shedding dynamics by PCR and/or culture available through September 8, 2020. We calculated the pooled median duration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 80 publications
4
115
1
3
Order By: Relevance
“…The short peak period may also be associated to fecal shedding patterns of the population contributing to the wastewater. It is noted that several current studies investigating fecal shedding timelines and intensity for SARS-CoV-2 may in fact be investigating the sickest of patients in a hospital setting ( Chen et al, 2020 ; Fontana et al, 2020 ), and so patterns may not reflect occurrences in the general population, where a significant quantity of patients will likely suffer from milder symptoms, or no symptoms at all ( Pan et al, 2020 ; Park et al, 2020 ). Furthermore, sicker or elderly patients may in fact “fall off” the wastewater monitoring efforts if bed pans or adult diapers are utilized as part of their treatment and convalescence in a hospital or retirement home ( Coelho et al, 2015 ; Tsang et al, 2017 ).…”
Section: Results Discussion and Implicationsmentioning
confidence: 99%
“…The short peak period may also be associated to fecal shedding patterns of the population contributing to the wastewater. It is noted that several current studies investigating fecal shedding timelines and intensity for SARS-CoV-2 may in fact be investigating the sickest of patients in a hospital setting ( Chen et al, 2020 ; Fontana et al, 2020 ), and so patterns may not reflect occurrences in the general population, where a significant quantity of patients will likely suffer from milder symptoms, or no symptoms at all ( Pan et al, 2020 ; Park et al, 2020 ). Furthermore, sicker or elderly patients may in fact “fall off” the wastewater monitoring efforts if bed pans or adult diapers are utilized as part of their treatment and convalescence in a hospital or retirement home ( Coelho et al, 2015 ; Tsang et al, 2017 ).…”
Section: Results Discussion and Implicationsmentioning
confidence: 99%
“…The association between severity of COVID-19 disease and duration of viral RNA shedding has already been widely reported ( Xu et al, 2020 , Du et al, 2020 , Zhou et al, 2020a , Liu et al, 2020a , Zheng et al, 2020 ). Indeed, although several studies have described similar ( To et al, 2020 , Cevik et al, 2020 , Yilmaz et al, 2021 ) or even longer ( Cevik et al, 2020 ) duration of viral RNA shedding in URT in mild compared to severe cases, the majority of reports found that patients with more severe illness shed viral RNA for a longer period of time ( Cevik et al, 2020 , Xu et al, 2020 , Du et al, 2020 , Zhou et al, 2020a , Liu et al, 2020a , Zheng et al, 2020 , Fontana et al, 2020 ). It is worth noting that the definition of severity among these studies is not homogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of mean and maximum recorded shedding periods for SARS-CoV-2 and other respiratory viruses after disease onset. Mean durations of SARs-CoV-2 shedding by PCR in 31 published larger cohort studies (total subjects=4150) [2, 37, 90–97] compared to those of RSV and IAV [1, 7–14]. Solid black lines indicate the mean value of all studies for each virus.…”
Section: The Acute Infection Modelmentioning
confidence: 99%